The SPARC Quasi‐Biennial Oscillation initiative. (27th July 2020) - Anstey, James A.; Butchart, Neal; Hamilton, Kevin; Osprey, Scott M.
Abstract: Introduction and background to the Stratosphere–troposphere Processes And their Role in Climate (SPARC) project, the QBOi, and the papers contained in this Special Section. Abstract : Vertical profile time series of equatorial monthly‐mean zonal‐mean zonal wind from the European Centre for Medium‐range Weather Forecasts ERA5 dataset. The data are shown using a logarithmic pressure scaling between (171.2 – 5.3) hPa.